Lovers, not fighters: Left politics and brandos costumes in Capitães de Abril - Sabine, Mark (Liverpool University Press, 2017)
The popularity of Maria de Medeiros’s Capitães de Abril [April Captains] (2000) has made it a significant reference point in perceptions and post-memory of the Portuguese revolution. This essay argues that the film presents the 25 April 1974 coup as a restitution of social justice predicated on the long-established notion of Portuguese brandos costumes [gentle customs]. By foregrounding both the April captains’ commitment to non-violent regime change, and their attitudes of humility, empathy and good humour, the film opposes them to an authoritarian regime whose arrogant, stubborn and brutal defenders repeatedly traduce ‘traditional’ national values. The endemic nature of brandos costumes is meanwhile implied by representing army conscripts and the common people as ill-suited to military engagement, but strongly disposed to ‘feminine’ values of love, solidarity, and compassion. Ultimately, Capitães’ appropriation of this national myth revises the gender politics of commemorations of the April Revolution, but reinforces paternalistic conceptions of Portuguese social organisation.